A secure and auditable logging infrastructure based on a permissioned blockchain. Issue 87 (November 2019) - Putz, Benedikt; Menges, Florian; Pernul, Günther
Abstract: Information systems in organizations are regularly subject to cyber attacks targeting confidential data or threatening the availability of the infrastructure. In case of a successful attack it is crucial to maintain integrity of the evidence for later use in court. Existing solutions to preserve integrity of log records remain cost-intensive or hard to implement in practice. In this work we present a new infrastructure for log integrity preservation which does not depend upon trusted third parties or specialized hardware. The system uses a blockchain to store non-repudiable proofs of existence for all generated log records. An open-source prototype of the resulting log auditing service is developed and deployed, followed by a security and performance evaluation. The infrastructure represents a novel software-based solution to the secure logging problem, which unlike existing approaches does not rely on specialized hardware, trusted third parties or modifications to the logging source.